2017
DOI: 10.1073/pnas.1618228114
|View full text |Cite
|
Sign up to set email alerts
|

Coding of navigational affordances in the human visual system

Abstract: A central component of spatial navigation is determining where one can and cannot go in the immediate environment. We used fMRI to test the hypothesis that the human visual system solves this problem by automatically identifying the navigational affordances of the local scene. Multivoxel pattern analyses showed that a scene-selective region of dorsal occipitoparietal cortex, known as the occipital place area, represents pathways for movement in scenes in a manner that is tolerant to variability in other visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
192
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(236 citation statements)
references
References 47 publications
16
192
6
Order By: Relevance
“…kitchen versus woods) and scene identity (e.g. our kitchen versus someone else's) using a combination of geometry and texture cues, whereas OPA is involved in the analysis of the local scene elements (Bonner and Epstein, 2017;Julian et al, 2018;Kamps et al, 2016;Lowe et al, 2017). Scenes that we recognize as distinct places might have identical layout and it is the textures and object ensembles that provide the crucial cues to where we are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…kitchen versus woods) and scene identity (e.g. our kitchen versus someone else's) using a combination of geometry and texture cues, whereas OPA is involved in the analysis of the local scene elements (Bonner and Epstein, 2017;Julian et al, 2018;Kamps et al, 2016;Lowe et al, 2017). Scenes that we recognize as distinct places might have identical layout and it is the textures and object ensembles that provide the crucial cues to where we are.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging studies suggest a role for human OPA in detecting navigationally important cues from visual scenes. A functional magnetic resonance imaging (fMRI) study demonstrated that OPA encodes possible paths in a visual scene (Bonner and Epstein, 2017), and if processing in the OPA is temporarily disrupted using transcranial magnetic stimulation (TMS), a person's ability to use boundaries in a navigational task is impaired .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to characterize how the visual system responds to views of reachable environments relative to views of full-scale scenes and close-up singleton objects. We found that (1), reachable environments activate distinct response topographies from both scenes and objects, with reachspace preferences in posterior ventral cortex and throughout the dorsal visual stream, (2) peaks in this preference are present in consistent locations across participants, allowing us to define ROIs in the posterior collateral sulcus, dorsally in occipto-parietal cortex, and the superior parietal lobule; (3) the response topographies of reachspace preferences are maintained when low-level features are controlled; (4) reachspaces elicit dissociable activity in scene and object ROIs, driving these regions to an intermediate degree; (5) reachspace-preferring regions have peripheral biases and (6) have distinctly higher response to the presence of multiple isolated objects over near-scale spatial layout with minimal object content, a combination that is unique among the ROIs explored here.…”
Section: Discussionmentioning
confidence: 99%
“…trampoline, dresser, arranged in a 3x2 grid on a white background; (4) 6 objects with small real world size, e.g. mug, watch, arranged in a 3x2 grid on a white background, and presented at the same visual size as the previous image condition; (5) reachable environments with all objects removed except the support surface; (6) reachspaces containing only a single object on the support surface; (7) vertical reachspaces, where the disposition of objects was vertical rather than horizontal, e.g. shelves, peg-boards; (8) regular reachspaces, i.e.…”
Section: Subjectsmentioning
confidence: 99%
“…the pathways for movements one may use to navigate through the scene) 25 . This profile is not only 193 important for visually-guided navigation and obstacle avoidance, but may also provide critical cues 194 indicating potential interactions with the local environment.…”
Section: Rsa 100mentioning
confidence: 99%